Profil Kemandirian dan Kreativitas Siswa SMA Sedes Sapientiae Semarang pada Pembelajaran Konsep Bioteknologi - Andrine Sulistyowati; Fenny Roshayanti (Perkumpulan Kualitama Edukatika Indonesia, 2022)
This study aims to analyze the profile of students' independence and creativity in learning biotechnology materials. This research is a descriptive qualitative research type with the research subject being 60 students of class XII MIPA Sedes Sapientiae Semarang in the academic year 2021 – 2022. The technique of collecting data is using a questionnaire about students' independence and creativity. The results showed that the students of class XII MIPA SMA Sedes Sapientiae Semarang had an independent and creative attitude in carrying out biotechnology projects to show a percentage of over 60% overall. Of course, the level of independence and creativity between one student and another varies. Many students tend to be less independent and innovative but also less dependent on others and lacking ideas. It can be seen from the research results that the figures range at most at 50-60%. Project-based learning model innovation using a scientific approach can be used to increase students' independence and creativity in learning.